Charles Baudelaire's The Swan and the vanishing Cityspace - Kuusamo Altti (Science publishing Group, 2025)
Altti Kuusamo’s article deals with the theme of loss and melancholy in Charles Baudelaire’s famous poem The Swan (Le Cygne, 1859) taking seriously into account one of the central subject matters, the image of the La Place du Carrousel, which referred to the courtyard between the Louvre and the Tuileries Palace and which had turned out to be a wasteland during Baudelaire’s mature work, in 1850s. In this way my article does not concentrate on the favourite subject of the flaneur in Charles Baudelaire’s poems, not even in the manner which Walter Benjamin made so fashionable. Instead, I’ll draw attention to the mental topography of the Carrousel site in Paris which seemed to be important to Baudelaire and also to his friends during 1840s. The feeling of the deserted quarters is in a way “humming” in the backyard of the Baudelaire’s poem. The motivation for my article lies in pondering why so many literary analysts of the poem, for example Walter Benjamin, Jean Starobinski, Yves Bonnefoy, Jonathan Culler, Stephanie Bundy and Ross Chambers, just to name some central literary figures, have not taken into account those images and metaphors which surround the name Carrousel in the poem. In the poem metaphors which are connected to ancient myths sweep the deserted paving stones of Place du Carrousel and illustrate the situation in which the demolition of the houses and streets of the western side of Louvre had taken place. Also the themes of loss and exile are closely tied to the central imagery of Carrousel close to Louvre.